Human Rights In The Novel Half The Sky By Wudunn And Kristof : Sociological Study - Zhafirah Farah Rizqikah; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
This research intends to analyze human rights violations and social conditions which affect human rights violations portrayed in the novel “Half the Sky” by Wudunn and Kristof. The research used descriptive qualitative research method with sociological study. There are two sources of data which are primary and secondary data. The primary data was taken from the novel “Half the Sky”. Meanwhile, the secondary data were taken from journal, theses, and article. The researcher used a sociological study to describe the social conditions that affect human rights in the novel “Half the Sky”. The result of this research, the researcher found the author’s way portrayed the kinds of human rights and the social conditions which affect human rights violations in the novel “Half the Sky” by Wudunn and Kristof.